2010
DOI: 10.3109/14767058.2010.511342
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous comparison of four neonatal pain scales in clinical settings

Abstract: DAN is a pain scale convenient for the use in clinical settings, especially if a fine distinction of magnitude of the present pain is not needed, whereas PIPP can be used if adequate equipment is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The present study showed that since the PIPP is more accurate in the assessment of more intense pains than low-intensity pains, it can detect subtle differences in the quantity and quality of pain. In addition, since PIPP is a combination of behavioral, physiological and contextual indicators, it is a valuable tool in premature infants' pain assessment (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that since the PIPP is more accurate in the assessment of more intense pains than low-intensity pains, it can detect subtle differences in the quantity and quality of pain. In addition, since PIPP is a combination of behavioral, physiological and contextual indicators, it is a valuable tool in premature infants' pain assessment (14).…”
Section: Discussionmentioning
confidence: 99%
“…They are divided into two types of uni-dimensional and multidimensional tools. The former measures only one aspect of pain that is the infants' behavioral responses, and the latter assesses behavioral and physiological responses simultaneously in combination with other contextual factors (14).…”
mentioning
confidence: 99%
“…Facial grimacing is a key component of most infant pain scales; elevations in heart rate and blood pressure may be more accurate when facial movements are decreased by sedation. Spasojevic and Bregun-Doronjski recently compared feasibility and variability among four commonly used pain scales; the authors found significant individual and overall variability among scales, with the DAN (Douleur aigu€ e du Nouveau-n e) having the least variability and the greatest ease of administration [Spasojevic and Bregun-Doronjski, 2010]. Whichever scale is used, staff training to use the scale and respond to it is key.…”
Section: Pain and Symptom Managementmentioning
confidence: 99%
“…The Modified Behavioral Pain Scale (MBPS) has also been frequently used to assess pain expression in young infants [24]. Table 15.1 provides an overview of the variables included in these specific pain scores [22][23][24][25][26][27][28][29][30].…”
Section: Limitations Of Assessment Of Distress and Pain In Neonatesmentioning
confidence: 99%
“…Pain assessment tools that quantify pain-related behavior include but are not limited to muscle tone, facial expression, position of the eyebrows and mouth, crying, muscular activity, or consolability. Table 15.1 provides a list of commonly used multidimensional pain scales in neonates [22][23][24][25][26][27][28][29][30]. (Refer to Chaps.…”
Section: Limitations Of Assessment Of Distress and Pain In Neonatesmentioning
confidence: 99%